The Impact of the TGT Type Cooperative Learning Model on Hitting Skills in Rounder Learning - Mardiansyah, Oktyanus; Wibowo, Sapto; Muhammad, Heryanto Nur; Ridwan, Mochamad (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2025)
This study aims to analyze the impact of implementing the cooperative learning model, Teams Games Tournament (TGT), on improving hitting skills in rounders lessons. The TGT cooperative learning model was chosen for its potential to enhance students’ motivation, engagement, and understanding through healthy competition and teamwork. The research method employed is an experimental design involving a control group and an experimental group. Data collected include hitting skill test results before and after the intervention. Data analysis was conducted using statistical tests to compare the improvement in hitting skills between the two groups. The findings of this study are expected to make a positive contribution to the development of more effective and engaging rounders learning strategies, as well as to improve the overall quality of physical education.